Why do women attend familial breast cancer clinics?. Issue 3 (1st March 2000) - Brain, Kate; Gray, Jonathon; Norman, Paul; Parsons, Evelyn; Clarke, Angus; Rogers, Cerilan; Mansel, Robert; Harper, Peter
Abstract : The increasing demand for genetic assessment for familial breast cancer has necessitated the development of cancer genetics services. However, little is known about the factors motivating the client population likely to approach these services. A cross sectional questionnaire survey of 1000 women with a family history of breast cancer was conducted to identify self-reported reasons for attending a familial breast cancer clinic and possible differences in the characteristics of women who were attending for diverse reasons. Before attendance at clinic, 833 women completed a baseline questionnaire (83% response rate). Women who gave personal risk (n=188), awareness of a family history (n=120), risk to family members (n=84), reassurance (n=69), genetic testing (n=65), breast screening (n=46), or prevention (n=39) as their main reason for attending were compared on demographic and medical variables, and on psychological variables including general anxiety, cancer worry, perceived risk, and attitudes towards prophylactic surgery and genetic testing. Important differences in the psychological characteristics of these groups were found, which were unrelated to reported family history. In particular, women who primarily wanted genetic testing felt extremely vulnerable to developing breast cancer, were more likely to be considering prophylactic surgery, and perceived fewer limitations of testing. Those who primarily wanted reassurance were highly anxious about the disease. We recommend that cancer genetics services take into consideration the informational and psychological needs and concerns of their client group.